2021
DOI: 10.1038/s41467-021-24563-1
|View full text |Cite
|
Sign up to set email alerts
|

GWAS of serum ALT and AST reveals an association of SLC30A10 Thr95Ile with hypermanganesemia symptoms

Abstract: Understanding mechanisms of hepatocellular damage may lead to new treatments for liver disease, and genome-wide association studies (GWAS) of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) serum activities have proven useful for investigating liver biology. Here we report 100 loci associating with both enzymes, using GWAS across 411,048 subjects in the UK Biobank. The rare missense variant SLC30A10 Thr95Ile (rs188273166) associates with the largest elevation of both enzymes, and this assoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 128 publications
(144 reference statements)
1
17
1
Order By: Relevance
“…GDM risk alleles at the lead SNV, and/or at variants in strong LD (European ancestry r 2 > 0.9) with it, have been previously associated, at genome-wide significance, with higher 2-h plasma glucose (2HPG) in pregnant women in the HAPO Study and two replication studies of European ancestry ( 30 ), as well as with higher birth weight of first child (likely via greater maternal glucose availability), higher own birth weight (fetal effect independent of the maternal effect on birth weight) and comparative height and body size at age 10 in UK Biobank ( 40 , 41 ) ( Supplementary Material, Table S9 ). The lead SNV is also associated, more strongly in women than men, with higher alanine aminotransferase (ALT) levels in UK Biobank ( 42 ). Elevated ALT levels in early pregnancy have been associated with the risk of subsequent development of GDM ( 43 ) and genome-wide, we observed positive genetic correlation between the two traits: r G (95% CI) 0.149 (0.005, 0.292).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GDM risk alleles at the lead SNV, and/or at variants in strong LD (European ancestry r 2 > 0.9) with it, have been previously associated, at genome-wide significance, with higher 2-h plasma glucose (2HPG) in pregnant women in the HAPO Study and two replication studies of European ancestry ( 30 ), as well as with higher birth weight of first child (likely via greater maternal glucose availability), higher own birth weight (fetal effect independent of the maternal effect on birth weight) and comparative height and body size at age 10 in UK Biobank ( 40 , 41 ) ( Supplementary Material, Table S9 ). The lead SNV is also associated, more strongly in women than men, with higher alanine aminotransferase (ALT) levels in UK Biobank ( 42 ). Elevated ALT levels in early pregnancy have been associated with the risk of subsequent development of GDM ( 43 ) and genome-wide, we observed positive genetic correlation between the two traits: r G (95% CI) 0.149 (0.005, 0.292).…”
Section: Resultsmentioning
confidence: 99%
“…We used LD Hub ( 58 ) to perform LD score regression ( 59 ) of the European ancestry association summary statistics for GDM on other glycaemic traits. We included T2D ( 33 ), fasting glucose ( 60 ), fasting insulin ( 60 ), fasting proinsulin ( 60 ), glucose 2 h post oral glucose tolerance test (adjusted for BMI) ( 61 ), HbA1c ( 62 ), HOMA-B ( 63 ), HOMA-IR ( 63 ), BMI ( 64 ), birth weight ( 41 ) and alanine aminotransferase ( 42 ). European ancestry association summary statistics for GDM were filtered so that only SNVs with minor allele frequency >0.01 was included before performing the LD score regression.…”
Section: Methodsmentioning
confidence: 99%
“…Liver injury is frequently accompanied by the higher activities of serum ALT and AST which are widely regarded as the most credible biochemical markers for assessing liver health. Clinic evidence also con rmed that the injury of liver tissue results in the hepatic ALT and AST being transferred to the circulation [21]. The activities of ALT re ect the injury of the cell membrane to a certain degree, while the activities of AST major re ect the injury of mitochondria to a certain degree [22].…”
Section: Discussionmentioning
confidence: 96%
“…After treatment, the main organs (heart, liver, spleen, lung, and kidney) of mice were taken for HE staining, and no obvious tissue damage was observed in each organ under the microscope (Figure A). Alanine aminotransferase (ALT), aspartate aminotransferase (AST), blood urea nitrogen (BUN), and creatinine (CREA) are commonly used indices to measure liver and kidney function in the clinic. , The results showed that ALT (Figure B), AST (Figure C), BUN (Figure D), and CREA (Figure E) were in the normal range, and there was no obvious liver and kidney function injury. This demonstrated once again that our synthesized nanocapsules have good safety at the animal level.…”
Section: Resultsmentioning
confidence: 99%